Kebijakan – Kebijakan Pada Tingkat Makro Untuk Mengatasi Kemiskinan - Feriadi Feriadi; Jasmine Damayanti; Muhammad Yasin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Poverty is a complex and multidimensional problem that requires a comprehensive approach to overcoming it. Policies at the macro level have an important role in reducing poverty through various economic, social and structural interventions. This research examines various macroeconomic policies that have been implemented to overcome poverty, including fiscal, monetary, trade policies and structural reforms. Analysis shows that effective policies must include increasing access to education and health, creating jobs, and strengthening social safety nets. In addition, the importance of coordination between national and regional policies is also emphasized to ensure optimal implementation and achievement of poverty alleviation targets. By understanding the impact and effectiveness of these policies, it is hoped that it can provide better recommendations for policy makers in designing appropriate strategies to reduce poverty in the future.